Sharkes in the north woods, or, Nish Na Bosh Na is nicer now - Zaring, Jane (Houghton Mifflin, 1982)
Four campers, trapped at a summer camp run by the Sharke family, plan a daring escape when the Sharkes hold the entire camp for ransom.